LUSOFONIA E HISTÓRIA: AFERIÇÕES DE PERTENÇA LUSO-AFÓNICAS - Mata, Inocência (2015)
Although it is still much debated, the term Lusophone continues to be widely used, as much as in the Portuguese-speaking areas as elsewhere. Its advocates state that it is a hugely economical term linguistically-speaking, used to designate a group of countries which share the same history. This latter perception stems from the idea that linguistic communion overlaps other affinities converging to affirm identity, which, judging from the ideological construction of the "language empire," goes far beyond the plenitude of the other assets belonging to these countries and peoples, taking into account the area in which they operate and the history-sharing with other communities, apart from their colonial heritage. The aim of the article is to discuss the meandering path taken to naturalise the idea which shows that, upon tuning affinities, language is the main driving force of identity and thus justifies the aptness of the conceptual term, Lusophone.